Análisis de la ventaja competitiva en la microempresa "Tierra Linda" del cantón Píllaro. - Chicaiza Ushiña, Consuelo Maribel (2018)
The present project analyzed the problem of the competitive advantage of the micro-company "Tierra Linda", so that the business products achieve a better place in the market. In fact, it was necessary to determine the relationship of manufacturing practices within the productive process of the industry. So, the analysis of the activities of the "Tierra Linda" microenterprise was achieved through observation, the productive, administrative and financial process and marketing which allowed to determine the positive and negative aspects of the industry. Once the existence of a competitive advantage was determined, a solution alternative was established to improve the competitiveness of the microenterprise. The research methodology helped to describe the difficulties, the application of appropriate methods, techniques and research instruments for the collection of information on the population that was the object of study. The research was important because it was able to establish a matrix (SWOT) strengths, opportunities, weaknesses, and threats of the business, which showed a strong impact, because in small companies have not developed inquiries of these characteristics, benefiting directly to the canned industrial sector